SEARCH FOR PROTEIN EBNA-1 P79 ANTI EBV IN SERUM OF PATIENTS REACHES ANY OF BREAST CANCER AND FROM WESTERN ALGERIA: Life Sciences-Biology - YAHIA R; ZAOUI C; MELOULI H; TAIBI F; SAHRAOUI T; ELKEBIR FZ (International Journal of Life Science and Pharma Research, 2022)
Breast cancer is in most countries, the most common cancer in women. It is the leading cause of death worldwide, there is a multifactorial disease where multiple events can be the cause of this disease, it is noted as an example genetic factors such asBRCA1 and BRCA2 genes and here ditary environmental factors, the notion of cancer virusis back in for cein the field of scientific research since the virus-induced cancers increasingly studied. Several families of viruses can induce cancer as the Epstein-Barr virus (EBV).The aim of the present study was to determine if there is a greater association of EBV infection with breast cancer patients as compared patients with nasopharyngeal cancer.We measured the levels ofanti-EBNA-1 P 79 in serum of these patients stored using Western blot technique. Patients with nasopharyngeal cancer were used as control group for comparison to serological analysis.Our study included 24 patients with breast cancer and 6 patients with nasopharyngeal cancer in western Algeria, from January 2009 to June 2009 in gynecology (CHUO), at the Pasteur Institute of Sidiférruj and Biology Laboratory of Development and Differentiation. 19 of 24 sera (79.16%) showed a positive serological profile, the 6 sera of patients reaches any of nasopharyngeal cancer (100%) were positive.The expression of EBNA-1P79 is seen in a significant proportion of sera from breast cancer, also for patients with nasopharyngeal cancer. Our results are consistent with those found in the literature.